2015
DOI: 10.1007/s11172-015-0897-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical studies of pyrimidin-4-ones

Abstract: Quantum chemical calculations of energies, electronic structures, and molecular geome tries of 3,5,6 trimethylthieno[2,3 d]pyrimidin 4 one (1), tricyclic 2,3 tri , 2,3 tetra , and 2,3 pentamethylene substituted 5,6 dimethylthieno[2,3 d]pyrimidin 4 ones (2-4), carboxy lic acids 5-8 resulting from oxidation of compounds 1-4 at the methyl group in position 5 of thienopyrimidine, methyl esters of these acids (9-12), and products of ipso nitration of esters (13-16) were performed in terms of the HF and DFT (B3LYP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…[23][24][25][26] This research also revealed that, in the absence of a substituent in position 3, the electrophilic ipsosubstitution of the methyl group by a nitro group with the formation of a 5-nitro derivative would take place. Thus, we found that, when the interaction of the compounds with electron-donating groups at N-3 position of the thienopyrimidine molecule was conducted with a nitrating mixture (HNO3/H2SO4 at 0-5 o C), instead of the ipso-nitration of methyl groups at C-5 the reaction proceeded in an unexpected direction, i.e., there was oxidation of the methyl groups.…”
Section: Ipso-nitration Of Heterocyclesmentioning
confidence: 80%
“…[23][24][25][26] This research also revealed that, in the absence of a substituent in position 3, the electrophilic ipsosubstitution of the methyl group by a nitro group with the formation of a 5-nitro derivative would take place. Thus, we found that, when the interaction of the compounds with electron-donating groups at N-3 position of the thienopyrimidine molecule was conducted with a nitrating mixture (HNO3/H2SO4 at 0-5 o C), instead of the ipso-nitration of methyl groups at C-5 the reaction proceeded in an unexpected direction, i.e., there was oxidation of the methyl groups.…”
Section: Ipso-nitration Of Heterocyclesmentioning
confidence: 80%